упростить 1. 19 cos^2 x — 9 + 19 sin^2 x


2. 17 cos^2 x — 5 + 17 sin^2 x
3. (sin^3 x — cos^3 x) / (1 + sinxcosx) +cosx — sinx
2. 17 cos^2 x — 5 + 17 sin^2 x

1. 19 cos^2 x — 9 + 19 sin^2 x=19(cos^2(x)+sin^2(x))-9=19-9=10

2. 17 cos^2 x — 5 + 17 sin^2 x=17(cos^2(x)+sin^2(x))-5=17-5=12

3. (sin^3 x — cos^3 x) / (1 + sinxcosx) +cosx — sinx=

= [(sinx-cosx)(sin^2(x)+sinxcosx+cos^2(x))/(1+sinxcosx)]+cosx-sinx=

= [(sinx-cosx)(1+sinxcosx)]/(1+sinxcosx)]+cosx-sinx=sinx-cosx+cosx-sinx=0

Добавить комментарий

Ваш e-mail не будет опубликован.